Dissecting lncRNA-mRNA competitive regulatory network in human islet tissue exosomes of a type 1 diabetes model reveals exosome miRNA markers - Tian, Fang; Gong, Xue; Wu, Jian j.; Long, Wei; Zhang, Xiaomeng; Yang, Fan (Frontiers in Endocrinology, 2022)
Emerging evidence shows that exosomes play a crucial role in the occurrence and development of diabetes and its complications. The molecules in exosomes can be regarded as important markers for the diagnosis of diseases. However, it is presently unclear the pathological association mechanism between exosomes and diabetes. In this study, transcriptome data and lncRNA regulatory association data of human pancreatic islet-derived exosome were integrated to construct the ceRNA network. Network analysis revealed that lncRNA with differential expression were primarily involved in islet insulin secretion signaling pathways, including Hippo, TGF-beta, Wnt, FOXO, Neurotrophin and ErbB signaling pathway. Further, combined with miRNA mediated competitive regulation and differential expression analysis results, potential markers of diabetes were revealed and validated in independent datasets. Finally, we analyzed the mechanisms of diabetes based on the competitive regulatory association and function of lncRNA. Our results suggest that lncRNA such as lncRNA PVT1, LINC00960 and hsa-miR-107 might be involved in inflammation response in T1DM , and the former lncRNA chose in the present study may serve as novel biomarkers and potential targets for the diagnosis and treatment of T1DM.